Incentivizing Social Learning for the Diffusion of Climate-Smart Agricultural Techniques - Adjognon, Guigonan Serge (World Bank, Washington, DC, 2022)
Unsustainable land use is a key threat to both economic development and environmental conservation in developing countries. This study implemented a randomized controlled trial in arid Burkina Faso to test the effectiveness of financial incentives in stimulating the adoption of sustainable land management practices (SLMPs). It did so in the context of a so-called cascade training program, in which some farmers were trained in the implementation of sustainable land management practices, who were then asked to disseminate their newly acquired knowledge and expertise to other farmers in their social networks. The study finds that offering payments conditional on adoption improves both the transfer of information from the trained to the peer farmers, as well as the peer farmers' sustainable land management practices adoption rates. Offering financial incentives thus mitigates two of the most important barriers to the adoption of sustainable land management practices – the (perceived) lack of private benefits and insufficient diffusion of the technical implementation information from the trained farmers to their peers. Finally, the study documents that adoption of sustainable land management practices generates substantial increases in crop productivity and agricultural income already after one agricultural cycle.